The truth about great white sharks - Cerullo, Mary M.; Rotman, Jeffrey L.; Wertz, Michael (San Francisco : Chronicle Books, 2000)
Describes the habits and behavior of the white shark and uses this information to dispel myths about this predator.
Includes bibliographical references (p. 46-47) and index.
School Library Journal starred.
Wilson's Children.
Wilson's Junior High School.
4.9.
4.9
Keywords: Sharks -- Juvenile literature; White shark -- Juvenile literature; Sharks; White shark; Sharks; White sharks